Validation of the 'drinking expectancy questionnaire for men who have sex with men' in Peru. - Vagenas, Panagiotis; Wickersham, Jeffrey A; Calabrese, Sarah K; Lama, Javier R; Benites, Carlos M; Pun, Monica; Sanchez, Jorge; Altice, Frederick L (Drug and alcohol review, 2015)
Alcohol use disorders are highly prevalent among men who have sex with men (MSM) in Peru, where the HIV epidemic is concentrated 100-fold greater among MSM than in the general population. Drinking expectancies have been associated with the intent to drink and engage in high-risk behaviours. Assessing them in this population may uncover attractive intervention targets that in turn can be used to reduce problematic drinking and risky sexual behaviours. The drinking expectancy questionnaire for MSM (DEQ-MSM) was developed to accurately measure drinking expectancies, specifically among MSM. This study aimed to validate this instrument for the first time in Spanish, in South America and among MSM in Peru.